Mengembangkan Minat dan Bakat Bahasa Inggris Siswa Melalui English Fun Base 2.0 di SMP Negeri 4 Sungguminasa - Hilal, Alda Alfiana; Waqqas, Hanin Khalishah; Hasriani G; Abdullah; Hasbi, Muh. (Jurusan Bahasa Inggris, 2024)
The development of potential interests and talents through enjoyable activities is crucial for personal growth. Every individual is born with inherent potential that needs to be nurtured. One effective method to hone these interests and talents is through participation in enjoyable competition activities. English Fun-Base 2.0 is an effort to develop the student's interest and talent in English. This research aims to find out how the activities should be integrated into inclusive and transformative English language learning to encourage students' interest and talent. The results show significant development in the interest and talents of students who participated in English Fun-Base activities, demonstrating that this approach is effective in creating enjoyable learning conditions for students based on the follow-up activities conducted.